Hypothalamic CRF1 receptor mechanisms are not sufficient to account for binge‐like palatable food consumption in female rats. Issue 10 (18th August 2017) - Micioni Di Bonaventura, Maria Vittoria; Ubaldi, Massimo; Giusepponi, Maria Elena; Rice, Kenner C.; Massi, Maurizio; Ciccocioppo, Roberto; Cifani, Carlo
Abstract: Objective: The present study evaluated the effect of systemic injection of the CRF1 receptor antagonist R121919, the corticosterone synthesis inhibitor metyrapone and central amygdala (CeA) injections of the nonselective CRF antagonist D‐Phe‐CRF(12–41) in rats in which binge eating was evoked by stress and cycles of food restriction. Method: Female rats were subjected or not to repeated cycles of regular chow food restriction/ad libitum feeding during which they were also given limited access (2 h) to palatable food. On the test day, rats were either exposed or not to the sight of the palatable food for 15 min without allowing access, before assessing food consumption. Results: Systemic injections of R121919, but not of the metyrapone, blocked binge‐like eating behavior. Restricted and stressed rats showed up‐regulation of crh1 receptor mRNA signal in the bed nucleus of the stria terminalis and CeA but not in basolateral amygdala (BLA) or in the paraventricular nucleus. Injection D‐Phe‐CRF(12–41) in CeA but not in the BLA‐blocked binge‐like eating behavior. Discussion: These findings demonstrate that extra‐hypothalamic CRF1 receptors, rather than those involved in endocrine functions, are involved in binge eating and the crucial role of CRF receptors in CeA. CRF1 receptor antagonism may represent a novel pharmacological treatment for binge‐related eating disorders.